Antigenotoxic properties of extracts of representatives of the genus Monarda introduced in the Urals: Antigenotoxic properties of Monarda (Indian Journal of Experimental Biology (IJEB), 2025)
Due to the fact that many antitumor drugs have genotoxicity, the aim of the study was to evaluate the antigenotoxic properties of extracts of the genus Monarda representatives using the Drosophila melanogaster model organism as an example. High IDC (Index of DNA-Comets) characterizes 0, 1% extracts of M. fistulosa var. fistulosa and M. fistulosa var. menthifolia when used both individually and together with etoposide. Whereas the extract of Monarda fistulosa var. media shows antigenotoxic properties by reducing the IDC and showing a unidirectional hypoexpressive effect relative to the sqh gene. Thus, the extract of Monarda fistulosa var. media is the most suitable protector against the effects of the anticancer drug etoposide.